Caregiver burden among caregivers of patients with mental illness: a systematic review and meta-analysis - Choy, Qing Cham; Ibrahim, Norhayati; Ching, Sin Siau; Kalaman, Clarisse Roswini; Meng, Chuan Ho; Yahya, Amira Najiha; Visvalingam, Uma; Roslan, Samsilah; Abd Rahman, Fairuz Nazri; Kai, Wei Lee (MDPI, 2022)
Due to the increasing importance of caregivers in the treatment outcomes of patients with mental illness, this study aimed to systematically review studies investigating the former’s caregiver burden and determine its prevalence. An open search, without filters, was conducted. Articles were selected from Medline, Scopus, and PubMed from inception to 30 April 2022 using the PRISMA protocol. Subgroup analyses examined the between-group differences by study setting, measurements used, and disorder type. A total of 5034 caregivers from 23 countries were included in this review. Thirty-nine studies were included in the systematic review, and, among them, twenty-six were deemed eligible for meta-analysis. The overall pooled prevalence of caregiver burden among caregivers of individuals with mental illness was 31.67% (95% CI = 26.22–37.12). Pooled prevalence was the highest among care recipients receiving treatment in a hospital setting (36.06%; 95% CI = 22.50–49.63), followed by the community and clinic settings. Caregiver prevalence values were higher for burden measured using the Zarit Burden Interview (38.05%; 95% CI = 27.68–48.43). compared with other instruments, and for carers of care recipients with psychosis (35.88%; 95% CI = 27.03–44.72) compared with those without. Thus, targeted interventions should focus on caregivers of patients in hospital settings and with psychotic symptoms.